The Influence of Mast Cell Mediators on Migration of SW756 Cervical Carcinoma Cells - M. Isolde Rudolph; Yadira Boza; Roger Yefi; Sandra Luza; Edilia Andrews; Alicia Penissi; Pablo Garrido; I. Gina Rojas (Elsevier, 2008)
The role of mast cell mediators on cervical cancer cell migration was assessed using an in vitro assay of scratch wound healing onto monolayers of HPV18-positive cervical carcinoma cells (SW756). Migration of SW756 cells was accelerated by co-culture with the mast cell line LAD2. This effect was inhibited by the H1R antagonist pyrilamine and the cannabinoid agonists 2-arachidonylglycerol (2AG) and Win 55,212-2. Therefore, the specific effects of histamine and cannabinoids on SW756 migration and LAD2 activation were analyzed. Histamine added to the in vitro assay of scratch wound healing either increased or inhibited SW756 migration rate by acting either on H1R or H4R, respectively. Cannabinoids acted on CB1 receptors to inhibit SW756 migration. Supernatants from SW756 cells stimulated LAD2 cell degranulation, which in turn was inhibited by cannabinoids acting via CB2 receptors. RT-PCR showed that SW756 expressed mRNA for CB1, CB2, H1R, H2R, and H4R. On the other hand, LAD2 expressed mRNA for all four HRs and CB2. The results suggest that mast cells could be contributing to cervical cancer cell invasion and spreading by the release of histamine and cannabinoids. Therefore, therapeutic modulation of specific mast cell mediators may be beneficial for cervical cancer treatment. Keywords:: mast cell, cervical cancer, histamine, cannabinoid, cell migration